Il mito piu antico dell'umanità - Knobloch, Johann
Enuma eliš shows conceptual correlation of winds, colors, "humors" (north-black-gall; east-yellow-bile; south-red-blood; west-white-phlegm); Iranian and other evidence for myth of four rivers and four primeval seas.